Formal specification approach in designing database system using Z - Julaily Aida, Jusoh; Mohd Yazid, Md Saman; Mustafa, Man (Asian Research Publishing Network, 2015)
The requirements for a software system set out what the system should do and define constraints on its operation and implementation. Traditionally, users express the requirement specification of system development by natural language. Natural language is ambiguous, thus the requirement specification statement may result in different apprehension among users, analysts and programmers. Anxieties have been raised by several relevant software developers about the weakness use of natural languages in documenting system requirements. Hence, one of the solutions to solve the problem in capturing user requirements is by using the formal specification approach. Formal specifications is an approach to solve the vagueness and contradiction in natural language descriptions by providing an unambiguous and precise specification. This approach can be validated and verified mathematically leading to the initial detection of specification errors. The use of a formal specification will reduces ambiguity between programmer and end-user while eliminates an errors during software development. If this is done, then we can carried out testing the system aligned to the user requirement specification. This work will discuss on how to implement formal specification approach in designing database system.